Examination and modelling of the influence of cutting parameters on the cutting force and the surface roughness in longitudinal turning - Bajić, Dražen (Strojniški vestnik, 2008)
This paper examines the influence of three cutting parameters on the surface roughness and the cutting force components in longitudinal turning. The cutting speed, the feed rate and the depth of cut have been taken as influential factors. Two modelling methodologies, namely regression analysis and neural networks, have been applied to experimentally determined data. Also, for both methodologies the ability of interpolation and extrapolation has been tested. Results obtained by neural network models have been compared to those obtained by regression models. Both methodologies give nearly similar results when interpolation is observed. However, regarding extrapolation neural network models give better results. In order to find the optimum values of the cutting parameters an optimization has been carried out.
Keywords: struženje; hrapavost; hitrost; podajanje; globina reza; nevronske mreže